2016
DOI: 10.1002/ana.24825
|View full text |Cite
|
Sign up to set email alerts
|

AV‐1451 tau and β‐amyloid positron emission tomography imaging in dementia with Lewy bodies

Abstract: Objective Patients with probable dementia with Lewy bodies (DLB) often have Alzheimer’s disease (AD)-related pathology. Our objective was to determine the pattern of positron emission tomography (PET) tau tracer AV-1451 uptake in patients with probable DLB, compared to AD, and its relationship to β-amyloid deposition on PET. Methods Consecutive patients with clinically probable DLB (n = 19) from the Mayo Clinic Alzheimer’s Disease Research Center underwent magnetic resonance imaging, AV-1451, and Pittsburgh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
167
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(199 citation statements)
references
References 47 publications
20
167
2
3
Order By: Relevance
“…Proteinopathy imaging studies confirm the spectrum nature of overlapping pathologies in neurodegenerative disorders [52, 53, 72]. Recent FDG PET imaging studies also demonstrate overlapping metabolic changes between DLB and the PCA variant of AD [24].…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Proteinopathy imaging studies confirm the spectrum nature of overlapping pathologies in neurodegenerative disorders [52, 53, 72]. Recent FDG PET imaging studies also demonstrate overlapping metabolic changes between DLB and the PCA variant of AD [24].…”
Section: Discussionmentioning
confidence: 88%
“…Shorter duration of disease was associated with greater AV-1451 uptake in the inferior temporal gyrus and precuneus in the DLB group. A subsequent larger [ 18 F]AV-1451 tau PET imaging study found that AV-1451 uptake was substantially more severe and extensive in AD compared to DLB patients [53]. Medial temporal uptake completely distinguished AD dementia (highest) from probable DLB (lowest).…”
Section: Tau Pet Imaging In Lewy Body Dementiasmentioning
confidence: 99%
See 2 more Smart Citations
“…Early data from tau imaging studies have reported conflicting findings on the relationships between amyloid deposition, tau deposition, and clinical profile in DLB 36, 37. Other important pathophysiological factors such as the extent and severity of Lewy body pathology remain unquantifiable until postmortem.…”
Section: Discussionmentioning
confidence: 99%